Minor hallucinations in Parkinson disease: A subtle symptom with major clinical implications - Lenka, Abhishek (Neurology, 2019)
OBJECTIVE: Psychosis is one of the most debilitating complications of Parkinson disease (PD). Although research on PD psychosis has been focused on the study of well-structured visual hallucinations (VH), currently accepted National Institute of Neurological Disorders and Stroke–National Institute of Mental Health diagnostic criteria emphasize minor hallucinations (MH) as the most common psychotic phenomena in PD. The objective of this review is to comprehensively describe the clinical and research advances on the understanding of MH and to provide future directions for obtaining further insights into their potential major implications for PD management and prognosis. METHODS: A PubMed search was done in November 2018 to identify articles on minor psychotic phenomena in PD. RESULTS: MH often precede the onset of well-structured VH and are associated with other nonmotor symptoms such as REM sleep behavior disorder and depression. The pattern of functional brain connectivity changes associated with MH involve visual-processing areas and attention control networks, which overlap with abnormalities described in patients with well-structured VH. The dysfunction of cortical networks in patients with MH may be an early indicator of a more widespread form of the disease. CONCLUSION: Although called “minor,” MH may have major clinical and prognostic implications. Further research is needed to establish whether MH are associated with a higher risk of disabling psychotic complications, cognitive deterioration, or a more accelerated disease progression. Understanding the early neurobiological underpinnings of MH may provide the background for future studies to identify the progressive dysfunction of neural circuits leading to more severe forms of psychosis in PD.